The Petsamo Board Game (1931) and Everyday Game Culture in Finland in the Interwar Period - Koskinen Karoliina; Suominen Jaakko (Finland, 2025)
The paper studies the Petsamo board game, published independently in Finland in
1931. This racing-genre game consisted of a game board map situated in the Petsamo
area in northern Lapland. Originally, Petsamo was mainly populated by Sámi people
and only officially became a part of Finland after the 1920 Treaty of Tartu between
Finland and Soviet Russia. After the Treaty, Petsamo became an arena for several
activities that can nowadays also be examined as borderland and cultural colonialism,
such as establishing new settlements, mineral prospecting, tourism, the production of
Petsamo-related artworks and so forth. In this paper, we approach the Petsamo game
within a larger cultural historical context and analyse the representations of Petsamo in
the game board and the instruction booklet as well as the activities of the designers of
the game and players who originally owned the copy of the game that is currently held
in the collection of the Turku Museum Centre. Thus, methodologically, the paper
presents a holistic microhistorical example of non-digital game history.
Proceedings of DiGRA 2023 conference